The prevalence of asymptomatic and symptomatic COVID-19 in a cohort of quarantined subjects - Al-Qahtani, Manaf (Int J Infect Dis, 2021)
BACKGROUND: The frequency of asymptomatic SARS-CoV-2 infection with viral spread is unclear. Asymptomatic SARS-CoV-2 infection development and progression was investigated in subjects undergoing mandatory quarantine on airport arrival. METHODS: 2714 subjects were tested for SARS-CoV-2 and all were quarantined for 2 weeks. Viral retesting was undertaken on symptom development and routinely at 14 days if asymptomatic. Asymptomatic, positive patients underwent viral testing every 2 days to determine viral clearance. RESULTS: 188/2714 (6.9%) patients became SARS-CoV-2 positive. On arrival, 136/188 tested positive, with 44/188 (23.4%) symptomatic and 92/188 (48.9%) asymptomatic. All 92 patients remained asymptomatic and were retested every 2 days until viral clearance. 2526 quarantined subjects remained virus free at 14 days. Viral clearance did not differ between symptomatic and asymptomatic patients (12.6 ± 1.0 days and 12.1 ± 0.4 days, respectively). Of the 52/188 (27.7%) testing negative on arrival, 27/52 subsequently became positive and developed symptoms 2–13 days after arrival. 25/188 (13.3%) remained asymptomatic and tested positive at day 14, with viral testing undertaken every 2 days in these subjects; of these, 24 remained asymptomatic, with viral clearance at 9.4 ± 0.7 days — less than for those who were asymptomatic on arrival (p < 0.002). CONCLUSION: Asymptomatic patients with COVID-19 were more prevalent than those exhibiting symptoms, and are an infection reservoir.